Global Weak Solutions for the Weakly Dissipative Camassa-Holm Equation (Journal of Partial Differential Equations, 2011)
In this paper we prove the existence and uniqueness of global weak solutions to the weakly dissipative Camassa-Holm equation.
Keywords: The weakly dissipative Camassa-Holm equation; global weak solutions